School Effect and Student Performance: a Latin American Assessment from PISA - Alves, Fabiana A. (2020)
Combining data from the last three editions of the Programme for International Student Assessment (PISA) with a multilevel approach, we aim to assess the effect of Latin American schools on student attainment and identify factors that contribute to their performance. It is found that family background, students’ characteristics and school community profile (peer effect) are paramount in explaining student performance. Regarding the school facilities, the disciplinary climate in the classroom and the existence and adequacy of pedagogical resources are the determinants that stood out the most. Moreover, the use of a multilevel approach is of utmost importance, since a considerable art of student performance variation is explained by differences among schools (school effect). Finally, the peer effect and the school effect suggest that the socioeconomic inequality in Latin American countries is quite important in determining the students’ performance.